2021
DOI: 10.22541/au.161606548.88251239/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive value of d-dimer/albumin ratio and fibrinogen/albumin ratio  for in-hospital mortality in patients with COVID-19            

Abstract: Introduction: Due to the high mortality of coronavirus disease 2019 (COVID-19), there are difficulties in the managing emergency department. We investigated whether the d-dimer/albumin ratio (DAR) and fibrinogen/albumin ratio (FAR) predicts mortality in the COVID-19 patients. Methods: A total of 717 COVID-19 patients who were brought to the emergency department from March to October 2020 were included in the study. Levels of d-dimer, fibrinogen, and albumin, as well as DAR, FAR, age, gender, and in-hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
(32 reference statements)
2
10
1
Order By: Relevance
“…Similarly in our research, when the fibrinogen to albumin ratio was considered, it was found to be 0.24 ± 0.3 in 272 patients who died, and 0.11 ± 0.6 in 275 patients who were recovered ( P = .000). In a recent study conducted in COVID‐19 patients, a correlation was found between high FAR and mortality, mentioning that FAR could be a better mortality predictor than fibrinogen alone 40 . In addition, the ROC analysis performed in our study shows that FAR is more sensitive and specific than fibrinogen, CRP and albumin in determining mortality.…”
Section: Discussionsupporting
confidence: 64%
“…Similarly in our research, when the fibrinogen to albumin ratio was considered, it was found to be 0.24 ± 0.3 in 272 patients who died, and 0.11 ± 0.6 in 275 patients who were recovered ( P = .000). In a recent study conducted in COVID‐19 patients, a correlation was found between high FAR and mortality, mentioning that FAR could be a better mortality predictor than fibrinogen alone 40 . In addition, the ROC analysis performed in our study shows that FAR is more sensitive and specific than fibrinogen, CRP and albumin in determining mortality.…”
Section: Discussionsupporting
confidence: 64%
“…Fibrinogen to albumin ratio (FAR) [49][50][51] and Urea to albumin ratio (UAR) [52][53][54] were studied in community-acquired pneumonia patients in some previous studies, and high FAR and UAR values were found to be associated with mortality. In a study conducted in COVID 19 patients, increased UAR ratio 55 and increased FAR 56 were associated with increased mortality risk. In our study, inflammatory biomarkers (CAR, NLR, FAR, and UAR) were found to have a statistically significant relationship with mortality while the AUC value of CAR was the highest in the ROC analysis for mortality.…”
Section: Discussionmentioning
confidence: 95%
“…[32][33][34] Küçükceran et al 15 found that DAR, as the ratio of D-dimer to albumin, can serve as a valuable predictor for mortality in COVID-19 patients. 15 However, the present results showed that DAR was similar between non-survivors and survivors among HBV-DeCi patients. Moreover, we did not find that DAR was associated with mortality in univariate analyses, and its predictive ability was inferior to that of the other four markers.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, recent studies showed that elevated plasma D-dimer can predict poor prognosis in patients with liver diseases. [32][33][34] Küçükceran et al 15 found that DAR, as the ratio of D-dimer to albumin, can serve as a valuable predictor for mortality in COVID-19 patients. 15 However, the present results showed that DAR was similar between non-survivors and survivors among HBV-DeCi patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation